Peran Media Sosial Dalam Mensosialisasikan Nilai Moderasi Beragama: Studi Analisis Platform Tiktok - Arlyah Septiyawati; Rofiyana Rofiyana; Dwi Ayu Septiyani; Achmad Tubagus Surur (JURNAL ILMIAH NUSANTARA, 2025)
This study examines how digital technology, particularly social media platforms like TikTok, might promote the values of religious moderation. This study looks at how digital technology, particularly social media platforms like TikTok, might promote the ideas of religious moderation. Nowadays, TikTok has become a sensation among Gen-Z, who are more likely to trust the content on the platform and look for information. This study aims to examine how social media, particularly TikTok, contributes to the promotion of religious moderation.This study employs a desk research methodology and a qualitative approach.Information about social media and religious reform was gathered from a variety of pertinent books. An examination of TikTok programs pertaining to religious reform was carried out in order to comprehend how these messages are disseminated and interpreted by the general public, particularly the younger generation. The findings demonstrate that TikTok effectively disseminates ideas of religious equality through hashtag usage and innovative projects. A broader audience has been exposed to content that promotes religious reform ideals, mostly as a result of users' active involvement in the production and dissemination of constructive information and content. The study's conclusion is that religious reform ideals can be widely disseminated via social media, particularly Tik Tok. Social media may play a significant role in increasing public awareness and fostering intercultural and religious peace in Indonesia with the correct digital communication plan.